Giudizio di appello nelle cause matrimoniali: “reiectio in limine” e limiti della prova (Stato, Chiese e pluralismo confessionale, 2021)
SOMMARIO: 1. Premessa - 2. Introduzione - 3. Il processo ordinario di appello nel M.P. Mitis Iudex - 4. L’appello nel processo abbreviato - 5. I limiti della prova in fase di appello.ABSTRACT: The article is the resumé of a speech originally delivered to the members of the Arcisodalizio della Curia Romana. It examines the canonical discipline in matrimonial case as it is contained in m.p. Mitis Iudex, by pope Francis, with whom the Pontiff has reformed the discipline of the canonical process in matrimonial cases. The author explaines the new discipline, compares it with the old one replaced, and discuss the points that seem to be problematic, proposing possible solutions in the light of the Roman Rota Jurisprudence of recent times.